Sperm motility and viability of experimental animals using different cryopreservatives - Won Yong Park; Byoung Boo Seo (The Korean Society of Animal Reproduction and Biotechnology, 2023)
In this study, an experiment was conducted in order to determine what cryopreservatives (CPVs) were more effective in supporting the motility and viability of sperm from experimental animals. The sperm of mice, rats, beagle dogs, and rabbits were frozen using different CPVs, including DMSO, TYB, and Sperm CryoProtec. The results from freezing the sperm of each laboratory animal in Sperm CryoProtec showed a high level of sperm motility and viability in sperm samples from mice, rats, and beagle dogs melted at the end of the first week. For rabbits, a high level of motility was observed in sperm thawed during the first week, whereas a high level of viability was observed in sperm thawed during the second week. The results of analysis of sperm motility and viability using different CPVs according to laboratory animals showed a significantly higher level of sperm motility (26.28%) and viability (36.20%) for mice in Sperm CryoProtec and the lowest levels of motility and viability were observed in DMSO (p < 0.05). Significantly higher levels of motility (27.94%) and viability (37.94%) were observed for rats in Sperm CryoProtec compared with TYB, which showed the lowest levels of motility and viability (p < 0.05). The study findings described above suggest that the selection of appropriate cryopreservatives is required for each experimental animal. This is because there are differences in the levels of sperm motility and viability of experimental animals depending on the CPVs that are typically used for freezing human sperm, including Sperm CryoProtec and TYB.